Analysis of efficiency of biodiesel production in a laboratory scale using a Network Data Envelopment Analisys - DEA methodology - Lopes, Rafaela Ferreira; Mello, João Carlos Correa Baptista Soares de; Silva, Ivenio Moreira da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2018)
This study aims to evaluate the biodiesel production performance in laboratorial scale, applying the Network Data Envelopment Analysis (DEA) model. This model allows to estimate the efficiency and volumes of different kind of oils used in tests. The input and output variables were obtained experimentally at the Laboratory of Post-Harvest Technology and Processing of Agricultural Products - LTPC of the Department of Engineering of the Federal Fluminense University. It was made an efficiency analysis in networks, separated in three stages. In the first stage, were used as inputs: oil, alcohol, catalysts and glycerol (undesirable output) in order to analyze the crude biodiesel production (first stage output). In the second stage, the intermediate product generated in the first stage, was used as input, in addition to acid and deionized water, having as output the washed biodiesel. And, in the third stage, the intermediate product generated in the second stage, washed biodiesel, was used as input, with the final product being the washed and filtered biodiesel. The results suggested that for the production stage, the first one, the smaller volumes were more efficient, but for the global stage the most efficient was the DMU Canola 200mL. The model presented scale returns and a raising scale factor, for all kinds of oil.